If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1a) + 4b = 3x + a Reorder the terms: 2(-1a + x) + 4b = 3x + a (-1a * 2 + x * 2) + 4b = 3x + a (-2a + 2x) + 4b = 3x + a Reorder the terms: -2a + 4b + 2x = 3x + a Reorder the terms: -2a + 4b + 2x = a + 3x Solving -2a + 4b + 2x = a + 3x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -2a + 4b + -1a + 2x = a + -1a + 3x Reorder the terms: -2a + -1a + 4b + 2x = a + -1a + 3x Combine like terms: -2a + -1a = -3a -3a + 4b + 2x = a + -1a + 3x Combine like terms: a + -1a = 0 -3a + 4b + 2x = 0 + 3x -3a + 4b + 2x = 3x Add '-4b' to each side of the equation. -3a + 4b + -4b + 2x = -4b + 3x Combine like terms: 4b + -4b = 0 -3a + 0 + 2x = -4b + 3x -3a + 2x = -4b + 3x Add '-2x' to each side of the equation. -3a + 2x + -2x = -4b + 3x + -2x Combine like terms: 2x + -2x = 0 -3a + 0 = -4b + 3x + -2x -3a = -4b + 3x + -2x Combine like terms: 3x + -2x = 1x -3a = -4b + 1x Divide each side by '-3'. a = 1.333333333b + -0.3333333333x Simplifying a = 1.333333333b + -0.3333333333x
| 7-f=2 | | 6-y=8 | | 5a=6-a | | 6+x/3=-2 | | -9x+8=-55 | | -5(y+1)-(-4y-8)=1 | | -3(2v+4)=12 | | 12(x+3)=4(3+3x) | | 3x-8=5x+6 | | (16y+4x)-(6x+10y)= | | t-8+3t=12 | | -24+21y=20 | | -3m=15 | | 3x+19=6x+34 | | 64p^3q-25pq^3= | | 3(6-y)=6 | | 1x+2=26 | | -9=4-n/2 | | (d-3)(d+5)=-12 | | 3y+17=47 | | .18(y-5)+.16=0.02-0.03(70) | | 2(w+4)=12 | | 2.5y=(y+5) | | 7.8(h-1)=6h+4+2h | | 5-y=3y+7 | | n/5=185 | | m+2/5=2m-3/8 | | 8(2x-5)=2(8x+1) | | x^2+10x-20=1 | | -1+13+11x+12x=24 | | -6z+6=-10-8z | | 9x+7=97 |